"I feel it is mine!" – Psychological ownership in relation to natural resources. (August 2017) - Matilainen, A.; Pohja-Mykrä, M.; Lähdesmäki, M.; Kurki, S.
Abstract: The use of natural resources often generates conflict among stakeholders. Conflict analysis and management in this sector has traditionally been based on compliance enforcement and/or education. Recently, however, the need for alternative approaches has been increasingly highlighted. In this study, we address the need for in-depth analysis, and introduce the theoretical concept of psychological ownership to improve the understanding and potential management of conflict situations. We suggest that ownership feelings may play a significant role both in successful co-operation, and in conflicts related to the use of natural resources. The study is qualitative in nature. The data consisted of two interview datasets related to nature tourism: nature tourism in private forests and bear watching safaris. We show that the ways the psychological ownership of stakeholder groups is constructed and taken into account in co-operative relationships are of the utmost importance for the sustainability and success of the interplay among stakeholders. Highlights: Stakeholders' opinions cannot be changed by focusing on explicit public arguments. Ownership feelings effect on cooperation and conflicts in use of natural resources. Psychological ownership –concept provides new approach to natural resource research. Respecting psychological ownership may help in natural resource conflict management.